A bio-based environmentally friendly impregnation system for fiber surfaces and impregnation treatment method
Patent Information
- Application Number
- CN202510463050.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-14
- Publication Date
- 2026-10-20
AI Technical Summary
[0007]为了解决非RFL浸渍体系均基于石油基化合物为原材料进行开发,原料成本昂贵的问题,本发明提供了一种纤维表面用生物基环保浸渍体系及浸渍处理方法
[0050]本发明提出了一种纤维表面用生物基环保浸渍体系,适用于各种纤维,处理后的纤维具有优异的粘合效果,可以达到替代传统RFL体系的目的。具体来说,
Smart Images

Figure BDA0005357712590000021 
Figure BDA0005357712590000031 
Figure BDA0005357712590000081
Abstract
Description
Technical Field
[0001] This invention relates to the field of fiber impregnation technology, and more specifically, to a bio-based environmentally friendly impregnation system and impregnation treatment method for fiber surfaces. Background Technology
[0002] Fibers and rubbers in fiber / rubber composites exhibit significant differences in polarity and modulus. When they form a composite material, the stress transfer at the interface determines the overall material performance. However, the large difference in polarity and modulus between fibers and rubber results in weak interfacial interaction. Currently, fiber surface impregnation is commonly used to enhance the adhesion between fibers and rubber. The most mature method is to impregnate the fiber material with resorcinol-formaldehyde-latex (RFL), which can significantly improve the adhesion between fibers and rubber. However, resorcinol and formaldehyde used in this method are highly toxic to humans and have been classified as carcinogens by the International Agency for Research on Cancer. Therefore, there is an urgent need to develop new, environmentally friendly fiber impregnation systems to replace the traditional toxic RFL impregnation system.
[0003] Patents US20150314644A1, US2012041113A1, and US5565507A disclose environmentally friendly impregnation solutions based on epoxy resins. Specifically, US2015314644A1 discloses an adhesive formulation consisting of rubber latex, an epoxy compound, and a polyamine with a molecular weight greater than 190 Daltons. This composition produces an adhesion level between the fiber skeleton material and the rubber compound that is close to that of conventional RFL systems. US2012041113A1 discloses an impregnation solution composed of epoxy resin, an amino curing agent, end-capped isocyanate, and rubber latex, which can be used to treat nylon and polyester fibers. US5565507A discloses an impregnation solution composed of a trifunctional or higher epoxy resin and a latex containing carboxyl, amino, or pyridine groups, which can be used to enhance the adhesion between woven fabrics and rubber.
[0004] Patents US20240368388A1, US2005147817A1, and US2005255773A1 disclose environmentally friendly impregnation solutions based on maleic anhydride-modified polymers. Specifically, US20240368388A1 discloses an impregnation system composed of maleic anhydride-modified polymer, epoxy resin, blocked isocyanate, curing agent, rubber latex, and reinforcing filler, achieving a treatment effect reaching RFL (Regenerative Laser Flask) level. US2005147817A1 discloses an impregnation solution composed of semi-esterified maleic anhydride-modified polybutadiene, carbon black, and latex, which can effectively improve the adhesion between fibers and EPDM rubber. US2005255773A1 discloses an environmentally friendly impregnation solution composed of maleic anhydride-modified polyolefin, maleimide resin, vinyl unsaturated carboxylic acid metal salt, and latex, which can significantly improve the adhesion between fibers and rubber.
[0005] Patents US2015315410A1 and US20150259560A1 disclose environmentally friendly impregnation solutions based on acrylic resin. US2015315410A1 discloses an impregnation solution composed of carboxyl-containing acrylic resin, epoxy resin, blocked isocyanate, and latex, which exhibits slightly better adhesion than RFL. US20150259560A1 discloses an impregnation solution composed of acrylic resin, epoxy compound, isocyanate, and rubber latex, used to improve the adhesion between fibers and between fabrics and rubber.
[0006] The aforementioned non-RFL environmentally friendly impregnation systems avoid the use of toxic substances such as resorcinol and formaldehyde; however, all of these non-RFL impregnation systems are developed based on petroleum-based compounds as raw materials, which are expensive; and due to various reasons, such as high raw material costs, complex configuration processes, and stringent process requirements, the aforementioned non-RFL environmentally friendly impregnation treatment technologies have not been commercialized. Summary of the Invention
[0007] To address the issue of high raw material costs in non-RFL impregnation systems, which are all developed based on petroleum-based compounds, this invention provides a bio-based environmentally friendly impregnation system and impregnation treatment method for fiber surfaces.
[0008] This invention uses plant-based polyphenols, bio-based aldehydes and waterborne polyurethane as the main components of the impregnation system, and combines them with rubber latex to form a bio-based environmentally friendly impregnation system for fiber surfaces.
[0009] The fiber surface treatment impregnation system provided by this invention uses only biological materials as raw materials, thus achieving bio-based and environmentally friendly impregnation system; moreover, it can achieve good curing effect in the impregnation system without the addition of isocyanate and additives, thereby achieving good interfacial adhesion effect.
[0010] One of the objectives of this invention is to provide a bio-based environmentally friendly impregnation system for fiber surfaces.
[0011] The impregnation system comprises the following components;
[0012] Each component is expressed in parts by weight:
[0013]
[0014]
[0015] Solvent A is an aqueous solvent, preferably water, and more preferably deionized water.
[0016] The plant-based polyphenols are selected from one or more of tea polyphenols, tannic acid, guaiacol, lignin, apigenin, resveratrol, naringenin, gallic acid, catechin, and apple polyphenols, preferably one or more of tea polyphenols, tannic acid, and lignin.
[0017] The bio-based aldehyde is selected from one or more of 5-hydroxymethylfurfural, vanillin, eugenol, cinnamaldehyde, benzaldehyde, phenylacetaldehyde, salicylaldehyde, and cinnamaldehyde, preferably one or more of 5-hydroxymethylfurfural, vanillin, and cinnamaldehyde.
[0018] As a specific approach, any one or more of the plant-based polyphenols and any one or more of the bio-based aldehydes can be combined. For example, tea polyphenols and 5-hydroxymethylfurfural can be combined as the main components of the impregnation system, or tannic acid and vanillin can be combined as the main components of the impregnation system. Compared to the combination of tannic acid and vanillin, the bio-based environmentally friendly impregnation system for fiber surfaces obtained by combining tea polyphenols and 5-hydroxymethylfurfural exhibits better H-extraction force, higher peel force, longer fatigue life, and better adhesion. When tea polyphenols and 5-hydroxymethylfurfural are used in combination, based on 100 parts by weight of solvent A, the amount of tea polyphenols is 0.2-0.4 parts by weight, and the amount of 5-hydroxymethylfurfural is 5.5-12 parts by weight.
[0019] The waterborne polyurethane is selected from one or more of aliphatic polyester polyurethane, aromatic polyester polyurethane, aliphatic polyether polyurethane, and aromatic polyether polyurethane, preferably one or more of aliphatic polyester polyurethane, such as aliphatic polyurethane dispersion resin.
[0020] The waterborne polyurethane is the second resin component in the impregnation system. It can provide a flexible molecular structure for the rigid phenolic resin network and improve the dynamic fatigue life of the fiber / rubber composite interface.
[0021] The rubber latex can be any one or more existing rubber latexes suitable for fiber surface treatment impregnation systems. Preferably, the rubber latex is selected from at least one of butyl phthalate latex, styrene-butadiene latex, styrene-butadiene-pyridine latex, chloroprene latex, nitrile latex, chlorosulfonated polyethylene latex, and natural latex; for example, the rubber latex is styrene-butadiene-vinylpyridine latex. The styrene-butadiene latex is preferably carboxylated styrene-butadiene latex; the nitrile latex is preferably carboxylated nitrile latex; and the natural latex is preferably epoxidized natural latex.
[0022] The solid content of the rubber latex can be a conventional solid content. Preferably, the solid content of the rubber latex is 20-60 wt%.
[0023] As a specific embodiment, the rubber latex is a styrene-butadiene-vinylpyridine latex with a solid content of 40 wt%.
[0024] The filler is an optional component. Compared to an impregnation system without filler, an impregnation system containing filler has better adhesive properties. Therefore, as a preferred embodiment, the bio-based environmentally friendly impregnation system for the fiber surface contains filler; based on 100 parts by weight of solvent A, the amount of filler is 0.05-0.5 parts by weight, preferably 0.15-0.2 parts by weight.
[0025] The filler can be any one or more existing fillers suitable for fiber surface treatment impregnation systems. As a preferred embodiment, the filler is selected from one or more of the following: nano-silica, carbon black, nano-titanium dioxide, nano-zinc oxide, nano-iron oxide, nano-calcium oxide, nano-calcium carbonate, carbon nanotubes, attapulgite, nano-cellulose, silicide, nano-aramid fiber, basalt fiber, nano whiskers, graphene oxide, montmorillonite, mica, kaolin, and hydrotalcite. Preferably, it is selected from one or more of the following: nano-cellulose, nano-silica, montmorillonite, and carbon nanotubes.
[0026] The filler is preferably a filler treated with a surface modifier. The surface modifier is selected from one or more of aminosilane coupling agents, epoxysilane coupling agents, alkylsilane coupling agents, isocyanate-based silane coupling agents, and polyether silane coupling agents, preferably from one or more of γ-aminopropyltriethoxysilane (KH550), γ-glycidoxypropyltrimethoxysilane (KH560), γ-methacryloyloxypropyltrimethoxysilane (KH570), γ-mercaptopropyltriethoxysilane (KH580), bis-[γ-(triethoxysilyl)propyl]tetrasulfide (Si69), and vinyltriethoxysilane (A151).
[0027] One of the objectives of this invention is to provide an impregnation system that can be used for treating various fibers. Specifically, the fibers can be one or more of the following: rayon, nylon 6, nylon 66, meta- or para-aramid fibers, polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyimide, and carbon fiber. The fibers can be selected from one or more of the following forms: monofilament, towed yarn, twisted yarn, canvas, and tire cord fabric.
[0028] When impregnating fibers using the impregnation system described in one of the invention's objectives, conventional impregnation methods can be employed. Depending on the fiber type and intended use, single-bath or double-bath impregnation treatments can be selected. For example, double-bath treatment is suitable for heavy-denier nylon cords, aramid cords, polyester cords, and aramid / nylon blended cords.
[0029] The second objective of this invention is to provide a method for impregnating the surface of fibers.
[0030] The impregnation method includes:
[0031] Step 1): Place the fiber in the impregnation system as described in one of the invention's objectives, and impregnate at 15-40°C for 2-60 seconds.
[0032] Step 2): After impregnation, remove the fiber and dry it at 100-150℃ for 1-10 minutes, then cure it at 180-260℃ for 1-10 minutes.
[0033] As a preferred embodiment: Before step 1), the pH of the impregnation system is adjusted to alkaline using an alkaline solution, preferably between 8.0 and 11.0. The alkaline solution may be ammonia.
[0034] As a preferred method: Before step 1), immerse the fiber in the impregnation solution at 15-40℃ for 2-30 seconds, then remove it and dry it at 100-150℃ for 1-10 minutes, and then cure it at 180-260℃ for 1-10 minutes. This is a double-bath treatment.
[0035] The impregnation solution can be a conventional impregnation solution. As a preferred embodiment, the impregnation solution comprises, by weight: 100 parts solvent; 0.5 to 4 parts epoxy resin, preferably 0.5 to 2.5 parts epoxy resin; and 2 to 10 parts blocked isocyanate, preferably 4 to 8 parts isocyanate.
[0036] The blocked isocyanate is a blocked isocyanate formed from an isocyanate and a capping agent. The blocked isocyanate can be any existing blocked isocyanate used in the art. Preferably, the isocyanate is selected from one or more of trimethyl-1,6-hexamethylene diisocyanate, tetramethylene diisocyanate, tetramethyl diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1,3-phenyl diisocyanate, 1,4-phenyl diisocyanate, isophorone diisocyanate, and diphenylmethane diisocyanate, more preferably diphenylmethane diisocyanate.
[0037] The epoxy resin can be a mono- or multi-component epoxy resin that is soluble in solvent A or rubber latex. Preferably, the epoxy resin is selected from one or more of the following: bisphenol A type epoxy resin, epoxidized linear phenolic resin, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, 1,2-propanediol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, diglycidyl ether, glycerol diglycidyl ether, trimethylolpropane diglycidyl ether, tetraphenol ethane tetraglycidyl ether epoxy resin, sorbitol diglycidyl ether, resorcinol diglycidyl ether type epoxy resin, and bisresorcinol formaldehyde tetraglycidyl ether; more preferably, it is selected from one or more of the following: glycerol diglycidyl ether, ethylene glycol diglycidyl ether, and sorbitol diglycidyl ether, which have good water solubility. As one embodiment, the epoxy resin is composed of a first epoxy resin and a second epoxy resin in any proportion, wherein the first epoxy resin is sorbitol glycidyl ether and the second epoxy resin is ethylene glycol diglycidyl ether and / or glycerol glycidyl ether.
[0038] An impregnation method for a fiber surface, one specific embodiment of which includes the following steps:
[0039] Step A): Impregnate the fibers in the impregnation solution;
[0040] Step B): Dry the fibers treated in step A), and then cure them;
[0041] Step C): Adjust the pH of the impregnation system described in one of the objectives of the invention to 8.0-11.0 using ammonia; place the fibers treated in step B) into the impregnation system for impregnation;
[0042] Step D): Dry and cure the fibers treated in step C);
[0043] In step A), the immersion temperature is 15-40℃ and the time is 2-30s;
[0044] In step B), the drying temperature is 100-150℃ and the time is 1-10 min;
[0045] In step B), the curing temperature is 180-260℃ and the time is 1-10 min;
[0046] In step C), the immersion temperature is 15-40℃ and the time is 2-60s;
[0047] In step D), the drying temperature is 100-150℃ and the time is 1-10 min;
[0048] In step D), the curing temperature is 180-260℃ and the time is 1-10 min.
[0049] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0050] This invention proposes a bio-based environmentally friendly impregnation system for fiber surfaces, suitable for various fibers. The treated fibers exhibit excellent adhesion, achieving the goal of replacing the traditional RFL system. Specifically,
[0051] 1. The raw materials used in the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention are derived from natural bio-based products. They do not contain harmful components such as resorcinol and formaldehyde. They are green and environmentally friendly, and will not cause harm to the environment or human body. They have good renewability and replace traditional petrochemical materials, thus having the advantage of saving ecological resources.
[0052] 2. The bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention has excellent adhesion, can significantly improve fatigue resistance, does not cause significant damage to the strength of the fiber, and does not affect its use.
[0053] 3. The bio-based environmentally friendly impregnation system for fiber surfaces provided by the present invention further regulates the modulus of the impregnation layer by adding nanofillers, and constructs a modulus transition layer between the fiber and the rubber, which can improve the interfacial adhesion.
[0054] 4. The impregnation system preparation process and fiber surface treatment process in this invention are simple and have industrialization prospects. Detailed Implementation
[0055] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.
[0056] Unless otherwise specified, all raw materials used in the embodiments and comparative examples of this invention are commercially available, and all equipment used is conventional production equipment. Specifically:
[0057] Tea polyphenols, brand name TP80, purchased from Jiangsu Dehe Biotechnology Co., Ltd.
[0058] 5-Hydroxymethylfurfural, CAS 67-47-0, purchased from Zhejiang Tangneng Technology Co., Ltd.;
[0059] Tannic acid, CAS1401-55-4, purchased from Shanghai Mairui Biochemical Technology Co., Ltd.
[0060] Vanillin, CAS121-33-5, purchased from Shanghai Myriel Biochemical Technology Co., Ltd.
[0061] Aliphatic polyurethane dispersion resin, brand name Impranil DL1537, purchased from Shanghai Yuanhe Chemical Co., Ltd.
[0062] Nanocellulose, grade XFJ107, was purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.
[0063] Styrene-butadiene-vinylpyridine latex (VP latex), grade VP-15, purchased from Jiangsu Yatai Chemical Co., Ltd.
[0064] Sorbitol glycidyl ether, CAS 68412-01-1, purchased from Nan Ya Epoxy Resin Co., Ltd.
[0065] ε-caprolactam-terminated diphenylmethane diisocyanate, brand name CBI 50, was purchased from Changzhou Keying Chemical Co., Ltd.
[0066] Resorcinol, CAS108-46-3, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0067] Formaldehyde, CAS 50-00-0, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0068] Example 1
[0069] A bio-based environmentally friendly impregnation system for fiber surfaces, the formulation of which is as follows by weight:
[0070]
[0071] Preparation method of the impregnation system: All components (except latex) were dissolved in deionized water at a predetermined weight ratio. The solution was vigorously stirred at 500 rpm for 6 hours at 25°C to obtain a mixed solution. Subsequently, styrene-butadiene-vinylpyridine latex was added to the mixed solution, and the mixture was vigorously stirred at 500 rpm for 2 hours at 25°C. During stirring, ammonia was added to adjust the pH of the solution to 10, thus obtaining a bio-based environmentally friendly impregnation system for fiber surfaces.
[0072] Impregnation method: Nylon 66 cord (930 dtex / 2) is impregnated in the impregnation system for 3 seconds, then dried and cured in an oven to obtain impregnated cord. The drying temperature is 150℃, the drying time is 72s, the curing temperature is 210℃, and the curing time is 72s.
[0073] Example 2
[0074] A bio-based environmentally friendly impregnation system for fiber surfaces, the formulation of which is as follows by weight:
[0075]
[0076] Preparation method of the impregnation system: All components (except latex) were dissolved in deionized water at a predetermined weight ratio. The solution was vigorously stirred at 500 rpm for 6 hours at 25°C to obtain a mixed solution. Subsequently, styrene-butadiene-vinylpyridine latex was added to the mixed solution, and the mixture was vigorously stirred at 500 rpm for 2 hours at 25°C. During stirring, ammonia was added to adjust the pH of the solution to 10, thus obtaining a bio-based environmentally friendly impregnation system for fiber surfaces.
[0077] Impregnation method: Nylon 66 cord (930 dtex / 2) is impregnated in the impregnation system for 3 seconds, then dried and cured in an oven to obtain impregnated cord. The drying temperature is 150℃, the drying time is 72s, the curing temperature is 210℃, and the curing time is 72s.
[0078] Example 3
[0079] A bio-based environmentally friendly impregnation system for fiber surfaces, the formulation of which is as follows by weight:
[0080]
[0081] Preparation method of the impregnation system: All components (except latex) were dissolved in deionized water at a predetermined weight ratio. The solution was vigorously stirred at 500 rpm for 6 hours at 25°C to obtain a mixed solution. Subsequently, styrene-butadiene-vinylpyridine latex was added to the mixed solution, and the mixture was vigorously stirred at 500 rpm for 2 hours at 25°C. During stirring, ammonia was added to adjust the pH of the solution to 10, thus obtaining a bio-based environmentally friendly impregnation system for fiber surfaces.
[0082] Impregnation method: Nylon 66 cord (930 dtex / 2) is impregnated in the impregnation system for 3 seconds, then dried and cured in an oven to obtain impregnated cord. The drying temperature is 150℃, the drying time is 72s, the curing temperature is 210℃, and the curing time is 72s.
[0083] Example 4
[0084] A bio-based environmentally friendly impregnation system for fiber surfaces, the formulation of which is as follows by weight:
[0085]
[0086] Preparation method of the impregnation system: All components (except latex) were dissolved in deionized water at a predetermined weight ratio. The solution was vigorously stirred at 500 rpm for 6 hours at 25°C to obtain a mixed solution. Subsequently, styrene-butadiene-vinylpyridine latex was added to the mixed solution, and the mixture was vigorously stirred at 500 rpm for 2 hours at 25°C. During stirring, ammonia was added to adjust the pH of the solution to 10, thus obtaining a bio-based environmentally friendly impregnation system for fiber surfaces.
[0087] Impregnation method: Impregnate nylon 66 cord (930 dtex / 2) in the impregnation system for 3 seconds, then dry and cure in an oven to obtain impregnated cord. The drying temperature is 150℃, the drying time is 80s, and the curing temperature is 210℃, the curing time is 80s.
[0088] Example 5
[0089] A bio-based environmentally friendly impregnation system for fiber surfaces, the formulation of which is as follows by weight:
[0090]
[0091]
[0092] Preparation method of the impregnation system: All components (except latex) were dissolved in deionized water at a predetermined weight ratio. The solution was vigorously stirred at 500 rpm for 6 hours at 25°C to obtain a mixed solution. Subsequently, styrene-butadiene-vinylpyridine latex was added to the mixed solution, and the mixture was vigorously stirred at 500 rpm for 2 hours at 25°C. During stirring, ammonia was added to adjust the pH of the solution to 10, thus obtaining a bio-based environmentally friendly impregnation system for fiber surfaces.
[0093] Impregnation method: Impregnate nylon 66 cord (1400 dtex / 2) in the impregnation system for 3 seconds, then dry and cure in an oven to obtain impregnated cord. The drying temperature is 150℃, the drying time is 80s, and the curing temperature is 210℃, the curing time is 80s.
[0094] Example 6
[0095] A bio-based environmentally friendly impregnation system for fiber surfaces, the formulation of which is as follows by weight:
[0096]
[0097] Preparation method of impregnation solution:
[0098] All components (except latex and nanocellulose) were dissolved in 85 parts of deionized water at a predetermined weight ratio. The solution was stirred vigorously at 500 rpm for 6 hours at 25°C using an electric stirrer. Styrene-butadiene-vinylpyridine latex was added, and the solution was stirred vigorously at 500 rpm for 2 hours at 25°C. During stirring, ammonia was added to adjust the pH of the solution to 10, thus obtaining a mixed solution.
[0099] Nanocellulose and 15 parts of deionized water were added to a beaker and stirred vigorously at 800 rpm for 1 hour at 25°C using an electric stirrer. Then, ultrasonic stirring was performed with a power of 400W for 1 hour to obtain a nanocellulose dispersion.
[0100] The nanocellulose dispersion was mixed with the above mixed solution and stirred vigorously at 500 rpm for 1.5 h at 25 °C using an electric stirrer to obtain a bio-based environmentally friendly impregnation system for fiber surface.
[0101] Impregnation method: Impregnate nylon 66 cord (1400 dtex / 2) in the impregnation system for 3 seconds, then dry and cure in an oven to obtain impregnated cord. The drying temperature is 150℃, the drying time is 80s, and the curing temperature is 210℃, the curing time is 80s.
[0102] Example 7
[0103] A bio-based environmentally friendly impregnation system for fiber surfaces, the formulation of which is as follows by weight:
[0104]
[0105] 0.15 parts of modified nanocellulose means that the nanocellulose in the modified nanocellulose is 0.15 parts.
[0106] Preparation method of impregnation system:
[0107] All components (except latex and nanocellulose) were dissolved in 85 parts of deionized water at a predetermined weight ratio. The solution was stirred vigorously at 500 rpm for 6 hours at 25°C using an electric stirrer. Styrene-butadiene-vinylpyridine latex was added, and the solution was stirred vigorously at 500 rpm for 2 hours at 25°C. During stirring, ammonia was added to adjust the pH of the solution to 10, thus obtaining a mixed solution.
[0108] Nanocellulose and 15 parts of deionized water were added to a beaker, and modifier KH550 / ethanol (KH550 / ethanol volume ratio 2:1, ethanol (purity ≥95wt%)) was added (KH550 amount is 10wt% of filler amount). The mixture was stirred vigorously at 300rpm for 1h at 25℃, and then ultrasonically stirred for 1h with a power of 400W to obtain modified nanocellulose dispersion.
[0109] The modified nanocellulose dispersion was mixed with the above mixed solution and stirred vigorously at 500 rpm for 1.5 h at 25 °C using an electric stirrer to obtain a bio-based environmentally friendly impregnation system for fiber surface.
[0110] Impregnation method: Impregnate nylon 66 cord (1400 dtex / 2) in the impregnation system for 3 seconds, then dry and cure in an oven to obtain impregnated cord. The drying temperature is 150℃, the drying time is 80s, and the curing temperature is 210℃, the curing time is 80s.
[0111] Example 8
[0112] The formula for the first bath impregnation solution, by weight, is as follows:
[0113] 1.5 parts of sorbitol glycidyl ether
[0114] 3.7 parts of ε-lactam-terminated diphenylmethane diisocyanate and 100 parts of deionized water.
[0115] Preparation method of the first bath impregnation solution: Sorbitol glycidyl ether, ε-caprolactam-terminated diphenylmethane diisocyanate and deionized water are added to a beaker in proportion and stirred vigorously at 500 rpm for 1 hour at 25°C using an electric stirrer.
[0116] The second bath impregnation solution (a bio-based environmentally friendly impregnation system for fiber surfaces) is formulated as follows by weight:
[0117]
[0118] Preparation method of the second bath impregnation solution: All components (except latex) are dissolved in deionized water at a predetermined weight ratio. The solution is stirred vigorously at 500 rpm for 6 hours at 25°C to obtain a mixed solution. Subsequently, styrene-butadiene-vinylpyridine latex is added to the mixed solution, and the mixture is stirred vigorously at 500 rpm for 2 hours at 25°C. During stirring, ammonia water is added to adjust the pH of the solution to 10; thus, the second bath impregnation solution is obtained.
[0119] Impregnation treatment method:
[0120] First, the high-denier nylon 66 (2100 dtex / 3) cord was placed in the first impregnation bath, immersed for 3 seconds at room temperature, dried at 150°C for 72 seconds, and cured at 230°C for 72 seconds. Then, the fiber was placed in the second impregnation bath, immersed for 3 seconds at room temperature, dried at 150°C for 72 seconds, and cured at 230°C for 72 seconds.
[0121] Example 9
[0122] The composition and preparation method of the first bath impregnation solution are the same as in Example 8.
[0123] The second bath impregnation solution (a bio-based environmentally friendly impregnation system for fiber surfaces) is formulated as follows by weight:
[0124]
[0125] The preparation method of the second bath impregnation solution is the same as in Example 8.
[0126] The impregnation treatment method is the same as in Example 8.
[0127] Example 10
[0128] The composition and preparation method of the first bath impregnation solution are the same as in Example 8.
[0129] The second bath impregnation solution (a bio-based environmentally friendly impregnation system for fiber surfaces) is formulated as follows by weight:
[0130]
[0131] 0.2 parts of modified nanocellulose means that the nanocellulose in the modified nanocellulose is 0.2 parts.
[0132] Preparation method of the second bath impregnation solution:
[0133] All components (except latex and nanocellulose) were dissolved in 85 parts of deionized water at a predetermined weight ratio. The solution was stirred vigorously at 500 rpm for 6 hours at 25°C using an electric stirrer. Styrene-butadiene-vinylpyridine latex was added, and the solution was stirred vigorously at 500 rpm for 2 hours at 25°C. During stirring, ammonia was added to adjust the pH of the solution to 10, thus obtaining a mixed solution.
[0134] Nanocellulose and 15 parts of deionized water were added to a beaker, and modifier KH550 / ethanol (KH550 / ethanol volume ratio 2:1, ethanol (purity ≥95wt%)) was added (KH550 amount is 10wt% of filler amount). The mixture was stirred vigorously at 300rpm for 1h at 25℃, and then ultrasonically stirred for 1h with a power of 400W to obtain modified nanocellulose dispersion.
[0135] The modified nanocellulose dispersion was mixed with the above mixed solution and stirred vigorously at 500 rpm for 1.5 h at 25 °C using an electric stirrer to obtain the second bath impregnation solution.
[0136] Impregnation treatment method: same as in Example 8.
[0137] Example 11
[0138] The composition and preparation method of the first bath impregnation solution are the same as in Example 8.
[0139] The second bath impregnation solution (a bio-based environmentally friendly impregnation system for fiber surfaces) is formulated as follows by weight:
[0140]
[0141] The preparation method of the second bath impregnation solution is the same as in Example 8.
[0142] The impregnation treatment method is the same as in Example 8.
[0143] Example 12
[0144] The composition and preparation method of the first bath impregnation solution are the same as in Example 8.
[0145] The second bath impregnation solution (a bio-based environmentally friendly impregnation system for fiber surfaces) is formulated as follows by weight:
[0146]
[0147] 0.15 parts of modified nanocellulose means that the nanocellulose in the modified nanocellulose is 0.15 parts.
[0148] The preparation method of the second bath impregnation solution is the same as in Example 10.
[0149] Impregnation treatment method: same as in Example 8.
[0150] Example 13
[0151] The composition and preparation method of the first bath impregnation solution are the same as in Example 8.
[0152] The second bath impregnation solution (a bio-based environmentally friendly impregnation system for fiber surfaces) is formulated as follows by weight:
[0153]
[0154] The preparation method of the second bath impregnation solution is the same as in Example 8.
[0155] First, the polyester (1670 dtex / 2) cord is placed in the first impregnation bath, immersed for 3 seconds at room temperature, dried at 150°C for 55 seconds, and cured at 230°C for 55 seconds. Then, the fiber is placed in the second impregnation bath, immersed for 3 seconds at room temperature, dried at 150°C for 55 seconds, and cured at 230°C for 55 seconds.
[0156] Example 14
[0157] The composition and preparation method of the first bath impregnation solution are the same as in Example 8.
[0158] The second bath impregnation solution (a bio-based environmentally friendly impregnation system for fiber surfaces) is formulated as follows by weight:
[0159]
[0160] 0.15 parts of modified nanocellulose means that the nanocellulose in the modified nanocellulose is 0.15 parts.
[0161] The preparation method of the second bath impregnation solution is the same as in Example 10.
[0162] Impregnation treatment method: same as in Example 13.
[0163] Example 15
[0164] The composition and preparation method of the first bath impregnation solution are the same as in Example 8.
[0165] The second bath impregnation solution (a bio-based environmentally friendly impregnation system for fiber surfaces) is formulated as follows by weight:
[0166]
[0167] The preparation method of the second bath impregnation solution is the same as in Example 8.
[0168] The impregnation treatment method is the same as in Example 8.
[0169] Example 16
[0170] The composition and preparation method of the first bath impregnation solution are the same as in Example 8.
[0171] The second bath impregnation solution (a bio-based environmentally friendly impregnation system for fiber surfaces) is formulated as follows by weight:
[0172]
[0173]
[0174] The preparation method of the second bath impregnation solution is the same as in Example 10.
[0175] Impregnation treatment method: same as in Example 8.
[0176] Comparative Example 1
[0177] Comparative Example 1 is a traditional RFL impregnation treatment. The RFL impregnation system formulation, by weight, is as follows:
[0178]
[0179] Preparation of RFL impregnation system: 0.1 parts sodium hydroxide and 100 parts deionized water were added to a beaker and stirred vigorously at 500 rpm for 10 min with an electric stirrer. Then, 3.7 parts resorcinol were added and stirred for 10 min. Finally, 5.4 parts of formaldehyde aqueous solution (37 wt%) were added and stirred at room temperature for 6 h to obtain a homogeneous reaction solution. 80 parts of VP latex (solid content 40 wt%) were added and stirred at room temperature for 20 h. Before the end of stirring, 1 part of ammonia water was added to finally obtain the RFL impregnation solution.
[0180] RFL impregnation treatment method: Impregnate nylon 66 cord (930 dtex / 2) in the impregnation system for 3 seconds, then dry and cure in an oven. The drying temperature is 150℃, the drying time is 72s, and the curing temperature is 225℃, the curing time is 72s.
[0181] Comparative Example 2
[0182] The impregnation system formulation and processing technology of Comparative Example 2 are the same as those of Comparative Example 1, except that the fibers are different. The cord treated in Comparative Example 2 is nylon 66 cord (1400 dtex / 2).
[0183] Comparative Example 3
[0184] Comparative Example 3 uses traditional RFL impregnation treatment. The two-bath RFL formulation is as follows:
[0185] The components of the first bath impregnation solution, by weight:
[0186] 1.5 parts of sorbitol glycidyl ether;
[0187] 3.7 parts of ε-lactam-terminated diphenylmethane diisocyanate;
[0188] 100 portions of deionized water.
[0189] The second bath impregnation solution components (bio-based environmentally friendly impregnation system for fiber surfaces), by weight:
[0190]
[0191] Preparation method of the first bath impregnation solution: Sorbitol glycidyl ether, ε-caprolactam-terminated diphenylmethane diisocyanate and deionized water are added to a beaker in proportion and stirred vigorously at 500 rpm for 1 hour at 25°C using an electric stirrer.
[0192] Preparation method of the second bath impregnation solution: Add sodium hydroxide and deionized water into a beaker, stir vigorously at 500 rpm for 10 min with an electric stirrer, then add resorcinol and stir for 10 min, and finally add formaldehyde aqueous solution (37 wt%) and stir at room temperature for 6 h to obtain a uniform reaction solution.
[0193] The above solution was added to styrene-butadiene-vinylpyridine latex (solid content 40wt%) and stirred at room temperature for 1 hour. Before the stirring was finished, ammonia was added to finally obtain RFL impregnation solution.
[0194] RFL impregnation treatment method: First, the fiber is placed in the first impregnation bath, impregnated at room temperature for 3 seconds, dried at 150°C for 72 seconds, and cured at 230°C for 72 seconds. Then, the fiber is placed in the second impregnation bath, impregnated at room temperature for 3 seconds, dried at 150°C for 72 seconds, and cured at 230°C for 72 seconds. The fiber is high-denier nylon 66 cord (2100 dtex / 3).
[0195] Comparative Example 4
[0196] The aramid cord (1670 dtex / 2) was treated with the first and second impregnation solutions prepared in Comparative Example 3. The impregnation treatment method was the same as in Comparative Example 3.
[0197] Comparative Example 5
[0198] The polyester cord (1670 dtex / 2) was treated with the first and second impregnation solutions prepared in Comparative Example 3.
[0199] RFL impregnation treatment method: First, place the polyester (1670 dtex / 2) cord in the first impregnation bath, impregnate for 3 seconds at room temperature, dry at 150°C for 55 seconds, and cure at 230°C for 55 seconds. Then, place the fiber in the second impregnation bath, impregnate for 3 seconds at room temperature, dry at 150°C for 55 seconds, and cure at 230°C for 55 seconds.
[0200] Comparative Example 6
[0201] The aramid-nylon hybrid cord (AF1670dtex / 2+PA1400dtex / 1) was treated with the first and second impregnation solutions prepared in Comparative Example 3. The impregnation treatment method was the same as in Comparative Example 3.
[0202] Performance testing
[0203] The fiber cords impregnated in Examples 1-16 and Comparative Examples 1-6 were subjected to H-pull-out test, peel test, interfacial fatigue life test and cord strength test. The results are shown in Tables 1 and 2.
[0204] H-Pull-out force test specimen preparation method: According to standard GB / T2942-2009, the standard rubber (the standard rubber formula adopts GB / T9101-2017) is completely wrapped on the impregnated cord, and then it is placed on a flat vulcanizing machine for vulcanization. The vulcanization temperature is 136℃, the vulcanization time is 50min, and the vulcanization pressure is 15MPa.
[0205] Peel strength test specimen preparation method: Refer to standard GB / T40725-2021, completely cover the impregnated cord with standard rubber to prepare peel test specimens, and finally place them on a flat vulcanizing machine for vulcanization. The vulcanization temperature is 160℃, the vulcanization pressure is 2.354MPa, and the vulcanization time is 20min.
[0206] Fatigue life test specimen preparation method: Refer to standard GB / T31333, completely cover the impregnated cord with standard rubber, and then place it on a flat vulcanizing machine for vulcanization. The vulcanization temperature is 136℃, the vulcanization pressure is 5MPa, and the vulcanization time is 50min.
[0207] Vulcanizing mold dimensions: mold cavity depth 2mm, length 250mm, width 170mm, each sample width 20mm, spacing between samples 6mm, 10mm reserved on each side of the mold, and the thickness of the cover plate and the mold base plate is not less than 10mm.
[0208] Preparation method of fiber cord tensile strength test specimen: Following standard GB32108-2015, the strength of the cord was tested by holding force after the cord was coated with adhesive. The test cord length was 250 mm, and the tensile speed was 300 mm / min.
[0209] The H-pull-out force of the fiber cord is tested according to GB / T2942-2009, the peel force is tested according to GB / T40725-2021, the fatigue life is tested according to GB / T39639-2020, and the tensile strength is tested according to GB / T32108-2015.
[0210] Table 1 Data on single-bath treatment of fiber cord
[0211]
[0212] Examples 1-7 and Comparative Examples 1-2 all used a single-bath method to treat the fiber cords. The cords used in Examples 1-4 and Comparative Example 1 were nylon 66 cords (930 dtex / 2), and the cords used in Examples 5-7 and Comparative Example 2 were nylon 66 cords (1400 dtex / 2).
[0213] Table 1 shows that compared to Comparative Example 1, the H-pull-out force of Examples 1-4 increased by 3.6-5.2%, the peel force increased by 2.6-5.3%, the fatigue life increased by 21.2-50.27%, and the tensile strength remained the same or even slightly increased. It is evident that Examples 1-4 exhibit superior adhesive and mechanical properties compared to Comparative Example 1. Specifically, the fatigue life of Examples 1-4 is significantly improved compared to Comparative Example 1, demonstrating better fatigue resistance. The impregnation system used in Examples 1-4 is the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention, while Comparative Example 1 uses a traditional RFL impregnation system. This indicates that compared to the traditional RFL impregnation system, the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention can further improve the adhesive properties of nylon 66 (930 dtex / 2), especially its fatigue resistance, without significantly damaging the strength of nylon 66 (930 dtex / 2) or affecting its use.
[0214] Table 1 shows that compared to Comparative Example 2, the H-pull-out force of Examples 5-7 increased by 0.8-9.4%, the peel force increased by 3.0-12.9, the fatigue life increased by 18.3-40.7%, and the tensile strength remained the same or even slightly increased. It is evident that Examples 5-7 exhibit superior adhesive and mechanical properties compared to Comparative Example 2. Specifically, the fatigue life of Examples 5-7 is significantly improved compared to Comparative Example 2, demonstrating better fatigue resistance. The impregnation system used in Examples 5-7 is the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention, while Comparative Example 2 uses a traditional RFL impregnation system. This indicates that compared to the traditional RFL impregnation system, the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention can further improve the adhesive properties of nylon 66 (1400 dtex / 2), especially its fatigue resistance, without significantly damaging the fiber strength or affecting its use.
[0215] Table 1 shows that compared to Example 5, the H-pull-out force, peel force, and fatigue life of Example 6 increased by 4.1%, 3.9%, and 9.5%, respectively, while those of Example 7 increased by 8.6%, 9.6%, and 18.9%, respectively. The tensile strength of Examples 6 and 7 is comparable to that of Example 5. Examples 5, 6, and 7 all use the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention. The difference lies in that Example 5 did not add filler, Example 6 added unmodified filler, and Example 7 added modified filler. This indicates that the addition of filler can further improve the H-pull-out force, peel force, and fatigue life, thereby further enhancing the adhesion and fatigue resistance between the fiber and rubber. Simultaneously, the modification of the filler is beneficial for improving its dispersion effect in the impregnation solution, and the adhesive effect of the impregnation system reinforced with modified filler is further improved compared to the system reinforced with unmodified filler.
[0216] Table 2 Data on fiber cord treatment using the double-bath method
[0217]
[0218] Examples 8-16 and Comparative Examples 3-6 all employed a two-bath method to treat the fiber cords. The cords used in Examples 8-10 and Comparative Example 3 were high-denier nylon 66 (2100 dtex / 3), the cords used in Examples 11-12 and Comparative Example 4 were aramid (1670 dtex / 2), the cords used in Examples 13-14 and Comparative Example 5 were polyester (1670 dtex / 2), and the cords used in Examples 15-16 and Comparative Example 6 were aramid / nylon 66 retwisted (A 1670 dtex / 1 + N 1400 dtex / 2).
[0219] Table 2 shows that compared to Comparative Example 3, the H-pull-out force of Examples 8-10 increased by 0.3-6.8%, the peel force increased by 0.8-8.5%, the fatigue life increased by 38-83.5%, and the tensile strength remained the same. It is evident that Examples 8-10 exhibit superior adhesive and mechanical properties compared to Comparative Example 3. Specifically, the fatigue life of Examples 8-10 is significantly improved compared to Comparative Example 3, demonstrating better fatigue resistance. The impregnation system used in Examples 8-10 is the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention, while Comparative Example 3 uses a traditional RFL impregnation system. This indicates that compared to the traditional RFL impregnation system, the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention can further improve the adhesive properties, especially the fatigue resistance, of high-denier nylon 66 (2100 dtex / 3), without significantly damaging the strength of high-denier nylon 66 (2100 dtex / 3) or affecting its use.
[0220] Table 2 shows that compared to Comparative Example 4, the H-pull-out force of Examples 11-12 increased by 3.6-10.0%, the peel force increased by 8.3-15.0%, the fatigue life increased by 18.9-71.6%, and the tensile strength remained the same with a slight increase. It is evident that Examples 11-12 exhibit superior adhesive and mechanical properties compared to Comparative Example 4. Specifically, the fatigue life of Examples 11-12 is significantly improved compared to Comparative Example 4, demonstrating better fatigue resistance. The impregnation system used in Examples 11-12 is the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention, while Comparative Examples 11-12 use the traditional RFL impregnation system. This indicates that, compared to the traditional RFL impregnation system, the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention can further improve the adhesive properties of aramid (1670 dtex / 2), especially its fatigue resistance, without significantly damaging the strength of aramid (1670 dtex / 2) or affecting its use.
[0221] Table 2 shows that compared to Comparative Example 5, Examples 13-14 exhibited improved H-pull-out force (2.0-5.0%), improved peel force (17.1-24.3%), and improved fatigue life (126.2-163.1%), while maintaining or slightly improving tensile strength. This demonstrates that Examples 13-14 possess superior adhesive and mechanical properties compared to Comparative Example 5. Specifically, Examples 13-14 show significantly improved peel force and fatigue life compared to Comparative Example 5, exhibiting better peel performance and fatigue resistance. The impregnation system used in Examples 13-14 is the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention, while Comparative Example 5 used a traditional RFL impregnation system. This indicates that, compared to the traditional RFL impregnation system, the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention can further improve the adhesive properties of polyester (1670 dtex / 2), especially its fatigue resistance, without significantly damaging the strength of the polyester (1670 dtex / 2) or affecting its usability.
[0222] Table 2 shows that, compared to Comparative Example 6, Examples 15-16 exhibited improved H-pull-out force (4.3-12.5%), peel force (9.7-19.4%), fatigue life (23.6-46.9%), and tensile strength (some improvement). This indicates that Examples 15-16 possess superior adhesive and mechanical properties compared to Comparative Example 6. Specifically, the fatigue life of Examples 15-16 is significantly improved, demonstrating better fatigue resistance. The impregnation system used in Examples 15-16 is the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention, while Comparative Example 6 used a traditional RFL impregnation system. This invention demonstrates that, compared to the traditional RFL impregnation system, the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention can further improve the bonding properties, especially the fatigue resistance, of aramid / nylon 66 retwisted fibers (A1670dtex / 1+N1400dtex / 2), without causing significant damage to the strength of aramid / nylon 66 retwisted fibers (A1670dtex / 1+N1400dtex / 2) or affecting its use.
[0223] Table 2 shows that compared to Examples 9, 11, 13, and 15, Examples 10, 12, 14, and 16 all exhibit improved H-pull-out force, peel force, and fatigue life, while their tensile strength is comparable. Examples 9, 11, 13, 15, 10, 12, 14, and 16 all utilize the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention; the difference lies in that Examples 9, 11, 13, and 15 did not add fillers, while Examples 10, 12, 14, and 16 added modified fillers. This indicates that modifying the filler improves its dispersion effect in the impregnation solution, and the addition of modified fillers can further enhance H-pull-out force, peel force, and fatigue life, thereby further improving the adhesion and fatigue resistance between the fiber and rubber.
[0224] The data in Tables 1 and 2 show that the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention has excellent adhesion. The adhesion strength of various cords (high-denier nylon 66, aramid, polyester, and aramid-nylon blends) exceeds the adhesion level of traditional RFL treatment, and its dynamic adhesion effect significantly surpasses that of the traditional RFL system. Furthermore, the tensile strength of high-denier nylon 66 cords, aramid cords, polyester cords, and aramid-nylon blends did not change significantly after impregnation, indicating that the bio-based environmentally friendly impregnation system for fiber surfaces provided by this invention does not damage the strength of the fiber itself and does not affect the fiber's performance.
Claims
1. A bio-based environmentally friendly impregnation system for fiber surfaces, characterized in that, The impregnation system comprises the following components; Each component is expressed in parts by weight: Solvent A 100 parts; Plant-based polyphenols: 0.1-5 parts, preferably 1.5-2.2 parts; Bio-based aldehydes: 1-15 parts, preferably 5-12 parts; 0.1-5 parts of waterborne polyurethane, preferably 1.5-3 parts; Sodium hydroxide 0.1-0.5 parts, preferably 0.2-0.4 parts; 50-150 parts of rubber latex, preferably 85-125 parts; 0-30 parts of filler, preferably 0-10 parts.
2. The impregnation system as described in claim 1, characterized in that, Solvent A is an aqueous solvent, preferably water, and more preferably deionized water.
3. The impregnation system as described in claim 1, characterized in that, The plant-based polyphenols are selected from one or more of tea polyphenols, tannic acid, guaiacol, lignin, apigenin, resveratrol, naringenin, gallic acid, catechin, and apple polyphenols, preferably one or more of tea polyphenols, tannic acid, and lignin.
4. The impregnation system as described in claim 1, characterized in that, The bio-based aldehyde is selected from one or more of 5-hydroxymethylfurfural, vanillin, eugenol, cinnamaldehyde, benzaldehyde, phenylacetaldehyde, salicylaldehyde, and cinnamaldehyde, preferably one or more of 5-hydroxymethylfurfural, vanillin, and cinnamaldehyde.
5. The impregnation system as described in claim 1, characterized in that, The waterborne polyurethane is selected from one or more of aliphatic polyester polyurethane, aromatic polyester polyurethane, aliphatic polyether polyurethane, and aromatic polyether polyurethane, preferably one or more of aliphatic polyester polyurethane.
6. The impregnation system as described in claim 1, characterized in that, The rubber latex is selected from at least one of butyl ester latex, styrene-butadiene latex, styrene-butadiene latex, chloroprene latex, nitrile latex, chlorosulfonated polyethylene latex, and natural latex; the styrene-butadiene latex is preferably carboxylated styrene-butadiene latex; the nitrile latex is preferably carboxylated nitrile latex; the natural latex is preferably epoxidized natural latex; or / and, The solid content of the rubber latex is 20-60 wt%.
7. The impregnation system as described in claim 1, characterized in that, The filler is selected from one or more of nano-silica, carbon black, nano-titanium dioxide, nano-zinc oxide, nano-iron oxide, nano-calcium oxide, nano-calcium carbonate, carbon nanotubes, attapulgite, nano-cellulose, ash, nano-aramid fiber, basalt fiber, nano whiskers, graphene oxide, montmorillonite, mica, kaolin, and hydrotalcite, preferably one or more of nano-cellulose, nano-silica, montmorillonite, and carbon nanotubes.
8. The impregnation system as described in claim 1, characterized in that, The filler is a filler treated with a surface modifier; the surface modifier is selected from one or more of aminosilane coupling agents, epoxysilane coupling agents, alkylsilane coupling agents, isocyanate-based silane coupling agents and polyether silane coupling agents, preferably from one or more of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, bis-[γ-(triethoxysilyl)propyl]tetrasulfide and vinyltriethoxysilane.
9. A method for treating the surface of a fiber, characterized in that, The processing method includes: Step 1) Place the fiber in the impregnation system as described in any one of claims 1-8, and impregnate at 15-40°C for 2-60 seconds: Step 2) Remove the fiber, dry it at 100-150℃ for 1-10 min, and cure it at 180-260℃ for 1-10 min.
10. The processing method as described in claim 9, characterized in that, Prior to step 1), the pH of the impregnation system is adjusted to alkaline using an alkaline solution, preferably between 8.0 and 11.0; or / and, Before step 1), immerse the fiber in the impregnation solution at 15-40℃ for 2-30 seconds, then remove it and dry it at 100-150℃ for 1-10 minutes, and then cure it at 180-260℃ for 1-10 minutes. By weight, the impregnation comprises: 100 parts solvent; 0.5 to 4 parts epoxy resin, preferably 0.5 to 2.5 parts; and 2 to 10 parts blocked isocyanate, preferably 4 to 8 parts.
Citation Information
Patent Citations
Adhesive composition for adhering textiles to EPDM rubber
US20050147817A1
Method for adhering fabric to rubber, treated fabric, and fabric-rubber composites
US20050255773A1
Adhesive composition for organic fiber cords, rubber-reinforcing material using same, tire and bonding method
US20120041113A1
Dipping material for cord fabrics and a production method thereof
US20150259560A1
Tyre for vehicle wheels
US20150314644A1
